Interaction Study Between Humin and Phosphate: Possible Environmental Remediation for Domestic Wastewater - de Oliveira, Daniella Araujo Vasconcelos; Botero, Wander Gustavo; Santos, Josué Carinhanha Caldas; da Silva, Ricardo Moutinho [UNESP]; Pitombo, Leonardo Machado; do Carmo, Janaina Braga; Rosa, Luana Maria Tavares; de Oliveira, Luciana Camargo (Springer Nature, 2017)
The increase in demand for food due to the rapid population growth in recent years has raised the use of fertilizers, particularly phosphate salts. This fact has contributed to the excess amount of phosphorus species in aquatic systems. This is due to the leaching of these species present in the fertilizers applied to the soil to aquatic environments and may lead to eutrophication in these environments. Substances capable of interacting with the phosphate in the aquatic environment are promising for the reduction on the environmental impact. The humin, an insoluble fraction of humic material, has potential for phosphate retention, behaving like a chelating resin. Thus, the purpose of this research was to study the interaction between humin and phosphate. The equilibrium time between humin and phosphate was 15 min, where hydrogenionic potential (pH) 4.0 was the most effective in the interaction process. In this pH, the humin retained 33% of phosphate added. The complexing capacity of the humin-phosphate system was 11.53 mg g−1. The adsorption studies indicated that the system follows a kinetic pseudo-second-order model. The Freundlich model was the most suitable to describe the phosphate adsorption process in humin. To evaluate the humin application in real systems, humin was added to the domestic wastewater. Sixteen percent of the total phosphate was adsorbed by the humin. Based on these results, humin has the potential to phosphate retention in domestic wastewater and could be used as a chelating resin minimizing environmental impact.
Keywords: Adsorption; Complexing capacity; Humin; Phosphate; Wastewater